Biopesticides: a good recipe from Niger - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1999)
There is good news about biopesticide studies at the national institute for agricultural research INRAN, Niger. At a time when artificial pesticides are moving outside the reach of most farmers, INRAN's researchers have demonstrated that effective...